Sistem Informasi Penilaian Kinerja Pegawai Berbasis Web Pada Operasi Perangkat Daerah Kantor Camat Rantau Utara Labuhanbatu - Surya Ramadhan; Sumitro Sarkum; Iwan Purnama (Universitas Bina Sarana Informatika, 2019)
The research information system Web-based Employee performance assessment aims to: 1) Designing a new system to improve a system that is being used today by KANTOR CAMAT RANTAU UTARA. 2) Makes a the website can be used by agencies to know the performance of the employees of the Office of the head of the northern region 3) increasing knowledge for the author and address problems that are being faced by companies/agencies. 4) as reference materials for research project next. As for the programming used in the writing of this research is programming websites using MySQL database and PHP, and Sublime Text for the creation of a php script. From the results of testing against the proposed system it can be stated that: 1) the proposed System can assist superiors in knowing the performance of officials in the exercise of his duties; 2) Supervisor can tell if employees carry out work according to his duties; 3) process data processing employees more quickly and accurately Keywords: Assessment, performance, PNS, PHP and MySQL.